Do ethnic patients report longer lung cancer intervals than Anglo‐Australian patients?: Findings from a prospective, observational cohort study. (26th July 2021) - Mazza, Danielle; Lin, Xiaoping; Walter, Fiona M.; Young, Jane M.; Barnes, David J.; Mitchell, Paul L.; Brijnath, Bianca; Martin, Andrew; O'Byrne, Kenneth J.; Emery, Jon D.
Abstract: Objective: Lung cancer patients from ethnic minorities have poorer outcomes than their Caucasian counterparts. We compared lung cancer intervals between culturally and linguistically diverse (CALD) and Anglo‐Australian patients to identify ethnic disparities. Methods: This was a prospective, observational cohort study comprising a patient survey and reviews of patients' hospital and general practice records. Across three states, 577 (407 Anglo‐Australian and 170 CALD) patients were recruited and their hospital records reviewed. The survey was returned by 189 (135 Anglo‐Australian and 54 CALD) patients, and a review was completed by general practitioners (GPs) of 99 (76 Anglo‐Australian and 23 CALD) patients. Survival and Cox regression analyses were conducted. Results: CALD patients had longer hospital diagnostic interval [median 30 days, 95% confidence interval (CI) 26–34] than Anglo‐Australian patients (median 17, 95% CI 14–20), p = 0.005, hazard ratio (HR) = 1.32 (95% CI 1.09–1.60). This difference persisted after relevant factors were taken into consideration, adjusted HR = 1.26 (95% CI 1.03–1.54, p = 0.022). CALD patients also reported longer prehospital intervals; however, these differences were not statistically significant. Conclusion: Target interventions need to be developed to address ethnic disparity in hospital diagnostic interval.